2018
DOI: 10.1039/c8ta00023a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reduction of CO2on defect-rich Bi derived from Bi2S3with enhanced formate selectivity

Abstract: An urchin-like sulphide-derived bismuth electrocatalyst was synthesised for CO2reduction and a maximum of 84.0% faradaic efficiency for formate formation was achieved. The origin of the activity of the sulphide-derived bismuth catalyst was explored and its defect-rich structure was responsible for the high formate selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(93 citation statements)
references
References 40 publications
7
85
0
1
Order By: Relevance
“…The obtained results were shown in Figure b. It could be seen that the formate FE (91 %) and current density (22 mA cm −2 ) could keep stable without any significant decreasing during the electrolysis for 23 h. The result is comparable with those reported in the previous literature, demonstrating that Bi 2 O 3 ‐A electrode catalyst has a potential application for CO 2 electroreduction.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The obtained results were shown in Figure b. It could be seen that the formate FE (91 %) and current density (22 mA cm −2 ) could keep stable without any significant decreasing during the electrolysis for 23 h. The result is comparable with those reported in the previous literature, demonstrating that Bi 2 O 3 ‐A electrode catalyst has a potential application for CO 2 electroreduction.…”
Section: Resultssupporting
confidence: 82%
“…Some investigations have indicated that Bi catalysts could effectively catalyze CO 2 reduction to form CO with high Faradaic efficiencies (FEs) in an aprotic solvent (e. g., MeCN) containing ion liquids ,. More interestingly, some researchers have recently reported that Bi with different microstructures as electrodes could catalyze the electroreduction of CO 2 to formate with high selectivity and high FE in aqueous solutions . These investigations greatly promote the development of Bi‐based electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] It has been widely accepted that the introduction of vacancies induces the formation of new energy levels,w hich can narrowt he band gap of the catalysts and thus enhance their light-harvesting ability.F or example, the introduction of oxygen vacanciess ignificantly improves the visible-light response in TiO 2 , [7,8] BiPO 4 , [9] Bi 5 O 7 Br, [10] BiOBr, [11] BiOCl, [12] BiO 2Àx , [13] and ZnO photocatalysts. [1][2][3][4][5][6] It has been widely accepted that the introduction of vacancies induces the formation of new energy levels,w hich can narrowt he band gap of the catalysts and thus enhance their light-harvesting ability.F or example, the introduction of oxygen vacanciess ignificantly improves the visible-light response in TiO 2 , [7,8] BiPO 4 , [9] Bi 5 O 7 Br, [10] BiOBr, [11] BiOCl, [12] BiO 2Àx , [13] and ZnO photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, Bi nanosheets with a few layers can be obtained. Among various synthetic approaches, an electrochemical transformation strategy has been exploited to successfully prepare 2 D materials . Fortunately, most of the extensively studied Bi‐based compounds, such as BiOX (X=Cl, Br and I), Bi 2 O 2 CO 3 , BiVO 4 , and BiWO 6 , also have a unique layered structure resulting from weak van der Waals bonding interactions along specific directions.…”
Section: Introductionmentioning
confidence: 99%